Hukum Taurat Menurut Rasul Paulus Dan Relevansinya - Pitta Uli Hutagalung; Krisda Mahdalena Sinaga (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2023)
The law is God's commandment that shows His love and will. For this reason, the law becomes something that is important to be applied in the lives of God's people. However, it seems that there are contradictions regarding the law in Paul's letters both among theologians and people in general, giving rise to various interpretations. This diversity of interpretations raises questions about what the true essence of the law is that can still be relevant for God's people to apply today. Therefore, this article wants to describe the theological meaning of the law in Paul's writings that are relevant to the practical application of God's people today. This effort is carried out by the author by reviewing the background of some of Paul's letters which describe the law, so that he can further extract the theological values of the law contained therein. Through this, it can be understood that the law is practically relevant today by understanding that the law is all forms of feelings and actions that emanate from the heart to manifest love for God and others